The Digitalization of Grocery Retail Business and the Change in Online Shopping - Petrova, Simeonka (Research Papers, 2023)
The main goal of the research is to interpret conceptual ideas about the digitalization of the grocery retail business, considering the change in consumer behavior regarding online shopping and, on this basis, to outline the emerging dependencies. The set research tasks correspond to the goal. The measurement of the manifest dependencies is achieved by the method of linear regression and correlation. Respondents in the study are individuals from the 27-member states of the European Union. The data for their budgets is for the period 2016 – 2021. The obtained results allow assessing the impact of digitalization on the change in consumer behavior in the online grocery shopping process.
Keywords: Digital transformation; Food retail business; Retailers; Online shopping; Digitization